2018
DOI: 10.1007/s00267-018-1066-x
|View full text |Cite
|
Sign up to set email alerts
|

Water, Forests, People: The Swedish Experience in Building Resilient Landscapes

Abstract: A growing world population and rapid expansion of cities increase the pressure on basic resources such as water, food and energy. To safeguard the provision of these resources, restoration and sustainable management of landscapes is pivotal, including sustainable forest and water management. Sustainable forest management includes forest conservation, restoration, forestry and agroforestry practices. Interlinkages between forests and water are fundamental to moderate water budgets, stabilize runoff, reduce eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For example, in Sweden, which was widely deforested in the 1800s, forest expansion together with intensive forest management has doubled the standing volume of forests over the last 100 years, at the same time as annual harvest has increased (Figure 2). This outcome was supported by forest policy that ensures harvest does not exceed growth, and forests are regenerated after harvest (Eriksson et al, 2018). A similar trend of increased forest carbon stock with simultaneous increase in harvest has occurred in Denmark (Nord‐Larsen et al, 2020), Finland (Luke, 2017) and in the southeast United States (Aguilar et al, 2020).…”
Section: Sourcing Biomass For Bioenergy and Effects On Forest Management And Forest Carbon Balancementioning
confidence: 96%
“…For example, in Sweden, which was widely deforested in the 1800s, forest expansion together with intensive forest management has doubled the standing volume of forests over the last 100 years, at the same time as annual harvest has increased (Figure 2). This outcome was supported by forest policy that ensures harvest does not exceed growth, and forests are regenerated after harvest (Eriksson et al, 2018). A similar trend of increased forest carbon stock with simultaneous increase in harvest has occurred in Denmark (Nord‐Larsen et al, 2020), Finland (Luke, 2017) and in the southeast United States (Aguilar et al, 2020).…”
Section: Sourcing Biomass For Bioenergy and Effects On Forest Management And Forest Carbon Balancementioning
confidence: 96%
“…We found that forested landscapes were negatively associated with chlorophyll a concentrations (Mixed Forest rho= −0.029, Deciduous Broadleaf Forest rho = −0.24) and appeared to be essential in limiting the amount of runoff that is bound for freshwater systems [63]. In forested landscapes, soil is more porous and prone to water infiltration which reduces surface runoff and increases nutrient uptake [64].…”
Section: Natural and Anthropogenic Land Covermentioning
confidence: 91%
“…Figure 2 shows the different steps in the theory of change (1)(2)(3)(4)(5) in grey circles, the boundary partners and stakeholders involved in the process, and their interlinkages. The MSP on Water and Food is displayed to the left, and the MSP for Water and Forests to the right, with links to the Water and Landscape MSP at the bottom that brings together inputs from all the different boundary partners.…”
Section: Msp Reportsmentioning
confidence: 99%
“…Landscape-wide approaches that integrate the development of agriculture, forestry, energy, and water are considered key to address complex environmental problems [1,2], and to avoid trade-offs between response options. Applying the landscape approach is particularly useful when integrated solutions are required to solve complex challenges related to sustainable development [3].…”
Section: Introductionmentioning
confidence: 99%